Perbaikan Manajemen Produksi Pasca Panen dan Pemasaran pada Usaha Peternakan Sapi Perah di Kota Padang Panjang - Rahmi Wati; Amna Suresti; Ida Indrayani; Ade Sukma; Hilda Susanty (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2019)
The dedication was held on 2 (two) groups of farmers in Padang Panjang, which Farmers Group Permata Ibu and Lembah Makmur. The problems that be founded were (1) the production of milk was still low, (2) the lacked of diversification of products and packaging technology, (3). lacked of market segmentation. These activities provided information to improve the quality and quantity of milk production. Providing products diversification Technologies such as making yogurt, ice cream and milk pudding method. Then all of these products were packed by using innovations such as the use of plastic cups and aluminum foil that has been labeled the farmer groups. Market expansion was conducted in several schools, cafes and restaurants in Padang Panjang City.